Meta-analysis on short-term exposure to ambient ultrafine particles and respiratory morbidity. (28th October 2020) - Samoli, Evangelia; Rodopoulou, Sophia; Schneider, Alexandra; Morawska, Lidia; Stafoggia, Massimo; Renzi, Matteo; Breitner, Susanne; Lanki, Timo; Pickford, Regina; Schikowski, Tamara; Okokon, Enembe; Zhang, Siqi; et al.
Aim: There is growing interest in the health effects following exposure to ambient particles with a diameter <100 nm defined as ultrafine particles (UFPs), although studies so far have reported inconsistent results. We have undertaken a systematic review and meta-analysis for respiratory hospital admissions and emergency room visits following short-term exposure to UFPs. Methods: We searched PubMed and the Web of Science for studies published up to March 2019 to update previous reviews. We applied fixed- and random-effects models, assessed heterogeneity between cities and explored possible effect modifiers. Results: We identified nine publications, reporting effects from 15 cities, 11 of which were European. There was great variability in exposure assessment, outcome measures and the exposure lags considered. Our meta-analyses did not support UFP effects on respiratory morbidity across all ages. We found consistent statistically significant associations following lag 2 exposure during the warm period and in cities with mean daily UFP concentrations <6000 particles·cm ‒3, which was approximately the median of the city-specific mean levels. Among children aged 0–14 years, a 10 000 particle·cm ‒3 increase in UFPs 2 or 3 days before was associated with a relative risk of 1.01 (95% CI 1.00–1.02) in respiratory hospital admissions. Conclusions: Our study indicates UFP effects on respiratory health among children, and during the warm season across all ages at longer lags. The limited evidence and the large heterogeneity of previous reports call for future exposure assessment harmonisation and expanded research. Studies on short-term exposure to ultrafine particles and respiratory admissions show large variability in the exposure assessment methodology. We found indications of effects in lower concentrations, children and during the warm period of the year. https://bit.ly/2zynMza